2019
DOI: 10.18203/2319-2003.ijbcp20191563
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding the importance of vitamin D and prevention of its deficiency among female undergraduate medical students

Abstract: Background: Vitamin D deficiency is a common nutritional disorder that has assumed epidemic proportion. One of the major reasons for the worldwide spread of this disorder has been deficient awareness about the importance of vitamin D, its benefits on health, and prevention of deficiency state across different populations. Vitamin D deficiency (VDD) is widely prevalent in this part of the country (Kashmir valley, India), the prevalence being higher in females. This study was conducted to assess the awareness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…In India, medical students' awareness about vitamin D insufficiency was likewise low; just 54% of medical students were aware of this devastating issue (Lmhao et al, 2017). Another study involving 113 female medical students in India found that students' knowledge of vitamin D, its advantages, deficiency and management was lacking (Nowreen & Hameed, 2019). Also, the awareness of Vitamin D was reported to be limited among Chinese medical students (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In India, medical students' awareness about vitamin D insufficiency was likewise low; just 54% of medical students were aware of this devastating issue (Lmhao et al, 2017). Another study involving 113 female medical students in India found that students' knowledge of vitamin D, its advantages, deficiency and management was lacking (Nowreen & Hameed, 2019). Also, the awareness of Vitamin D was reported to be limited among Chinese medical students (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Participants had poor knowledge regarding sufficient serum levels, only 20.35% knew about other effects of deficiency, only 19.46% knew about recommended daily allowance, and only 7.96% knew about the adequate sun exposure. 19 Most of the participants reported newspaper, magazines and social media as the most common source of information about vitamin D and its benefits. Very few participants mentioned visiting antenatal clinic or hospitals as source of information.…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan pengetahuan responden mengenai defisiensi vitamin D dapat menyebabkan kanker masih cukup rendah, yaitu sebesar 18,92% pada responden obesitas dan 24,32% pada responden non-obesitas. Defisiensi vitamin D dapat terus terjadi akibat kurangnya pengetahuan dan praktik terhadap penggunaan vitamin D. Beberapa akibat dari defisiensi vitamin D adalah mempercepat keropos tulang dan menyebabkan beberapa risiko kanker seperti kanker usus besar, payudara, prostat, dan ovarium (Garland et al, 2006;Nowreen & Hameed, 2019)…”
Section: Pengetahuan Penggunaan Vitamin Dunclassified